Antiplatelets in acute coronary syndrome in Poland – from guidelines to clinical practice - Tubek, Stanisław; Kuliczkowski, Wiktor; Gąsior, Mariusz; Gierlotka, Marek; Kubica, Jacek; Budaj, Andrzej; Witkowski, Adam; Reczuch, Krzysztof; Ponikowski, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Acute coronary syndrome is a factor for poor prognosis and recurrent cardiovascular events. Adequate antiplatelet therapy is crucial in patients with the acute coronary syndrome for risk reduction. Such treatment is well described in four documents issued by the European Society of Cardiology, which precisely illustrate the use of antiplatelets in the settings of ST-elevated and non-ST elevated myocardial infarction. Despite its unquestioned role in the treatment of acute coronary syndrome, recent real-world-data from Polish registries reveal poor adherence to the guidelines-recommended antiplatelet treatment in Poland. Thus, we present here a comprehensive review of the use of antiplatelets in the settings of the acute coronary syndrome. Each phase of the treatment, i.e. pre-hospital, in-hospital and post-hospital, is discussed separately for a better understanding of the decision-making process at each step. We also present unpublished data from Polish registries (e.g. PL-ACS 2019, National Registry of Procedures of Invasive Cardiology, RECEPTOmetrPEX panel) regarding adherence to the guidelines-recommended treatment in Poland, thus highlighting the points of care which should be immediately improved. It has to be stressed here that careful assessment of ischaemic and bleeding risk has to be performed in each patient with acute coronary syndrome individually and repeated at successive phases of the treatment. Only such an approach allows for appropriate antiplatelet therapy tailoring.